Transformation Islamic Education In Indonesia (Journal Intellectual Sufism Research (JISR), 2021)
Islamic boarding school in its dynamic is regarded to have its own identity which is termed with subculture by KH. Abdurrahman Wahid. Honestly, it must be admitted that there is a certain tradition that grows and thrives in Islamic boarding school society. However, it is not a reality outside of  Islamic boarding school society. Undeniably, when the outside environment begins incessant with modernization issues, the â€œuniquenessâ€ in Islamic boarding school environment makes Islamic boarding school tradition more lively and interesting to be discussed. Environment Islamic boarding schools implication in modern time is less known and marginal, which slowly change to be something interesting among scientists and academics. One of its pieces of evidence is the emergence of an idea from part of the Islamic education observers with an educational modern system to present alternative education discourse. It is in line with Islamic boarding schools whose progress is identical with Islamic education that experiences a transformation along with changes of accompanying situation.